Antifungal dimeric chalcone derivative kamalachalcone E from Mallotus philippinensis - Kulkarni, Roshan R.; Tupe, Santosh G.; Gample, Suvarna P.; Chandgude, Macchindra G.; Sarkar, Dhiman; Deshpande, Mukund V.; Joshi, Swati P. (Natural Product Research, 2014)
From the red coloured extract (Kamala) prepared through acetone extraction of the fresh whole uncrushed fruits of Mallotus philippinensis, one new dimeric chalcone (1) along with three known compounds 1-(5,7-dihydroxy-2,2,6-trimethyl-2H-1-benzopyran-8-yl)-3-phenyl-2-propen -1-one (2), rottlerin (3) and 4 `-hydroxyrottlerin (4) were isolated. The structure of compound 1 was elucidated by 1D and 2D NMR analyses that included HSQC, HMBC, COSY and ROESY experiments along with the literature comparison. Compounds 1-4 were evaluated for antifungal activity against different human pathogenic yeasts and filamentous fungi. The antiproliferative activity of the compounds was evaluated against Thp-1 cell lines. Compounds 1 and 2 both exhibited IC50 of 8, 4 and 16 mu g/mL against Cryptococcus neoformans PRL518, C. neoformans ATCC32045 and Aspergillus fumigatus, respectively. Compound 4, at 100 mu g/mL, showed 54% growth inhibition of Thp-1 cell lines.
Keywords: 4 `-hydroxyrottlerin; antifungal; dimeric chalcone; kamalachalcone E; Mallotus philippinensis; rottlerin

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives